Ефективність використання добрив у сівозміні залежно від способів основного обробітку ґрунту - Десятник, Лідія Модестовна; Desyatnyk, lLidiya; Шевченко, Михайло Семенович; Shevchenko, Mikhail; Швець, Наталя Володимирівна; Shvetsʹ, Natalya; Шевченко, Сергій Михайлович; Shevchenko, Sergiy (Інститут зернових культур НААН, Україна, 2018)
Наведено аналіз експериментальних даних, одержаних в стаціонарному польовому дослід з вивчення ефективності мінеральних добрив на фоні мінімізації обробітку грунту та використання побічної органічної продукції. Встановлено, що вищий приріст урожайності за таких умов забезпечили пшениця озима і кукурудза на зерно, в той час як горох і ячмінь ярий суттєво поступалися їм за показниками продуктивності. Мінімізація основного обробітку грунту шляхом заміни оранки мілким розпушуванням грунту дисковими знаряддями і прямою сівбою супроводжувалась зниженням фізичної окупності мінеральних добрив внаслідок локалізації їх у верхньому шарі чорнозему звичайного. На підставі багатофакторного аналізу експериментальних даних розроблена модель алгоритмів екологічних, господарських і економічних показників. Встановлено, що значного підвищення ефективності використання мінеральних добрив можна добитися за рахунок вирощування високопродуктивних культур і розущільнення орного шару. При значному різноманітті економічних показників в агротехнологічній схемі стаціонарного досліду по всіх фонах обробітку грунту і культурах сівозміни прибутковість виробництва від застосування добрив підвищувалась найбільш стабільно.The analysis of experimental results in a stationary field experiment on the study of the efficiency of mineral fertilizers on the background of minimization of soil cultivation and the use of by-products of organic products is presented. It was found that higher yields ensured winter wheat and corn for grain, while peas and barley grew considerably inferior to productivity. Minimization of the main cultivation of soil by replacing plows in shallow loosening with disk implements and direct sowing was accompanied by a decrease in the physical recoupment of mineral fertilizers due to localization in the upper layer of black earth. On the basis of multivariate analysis of experimental data, a model of algorithms for ecological, economic and economic indicators was developed. It has been established that significant increase in the efficiency of mineral fertilizers can be achieved through the cultivation of high-yielding crops and the dilution of the arable soil layer. With a significant variety of economic indicators in the agrotechnological scheme of stationary experiments on all the backgrounds of soil cultivation and crop rotation, the indicators of profitability of production from the use of fertilizers grew most stably. On the basis of the experimental data obtained, the principles of optimization of the mineral fertilizer dispersion model in the soil are developed, which can be effectively regulated by the movement of soil mass during soil cultivation. The model of maximum efficiency of mineral fertilizers is based on a uniform distribution of nutrients in the arable soil layer.The narrowing of the localization of the main elements of nutrition is accompanied by a decrease in the yield of crops of grain-growing crop rotation due to the formation of a smaller mass of the root system. Along with this, the negative effects of soil compaction when minimizing cultivation are manifested in the mechanical deformation of branching of the roots. Therefore, the advantage should be given to differentiated soil cultivation. Among the crops of crop rotation, the largest mass of organic matter left behind corn (4,34 tons/ha), and the minimum sunflower (2,24 tons/ha), which determined the potential of biological soil activity. Reducing the depth of the basic soil cultivation is accompanied by an increase of soil hardness and deterioration of its water absorption, which enhances conservative processes and inhibits the decomposition of organic matter. Biological activity of the soil on the background of plowing exceeds the direct sowing by 15–20 %.
Efficiency of fertilizers using in crop rotation depending on the methods of basic soil cultivation
Keywords: добрива; fertilizers; сівозміна; crop rotation; обробіток грунту; soil cultivation; ефективність; efficiency; окупність; recoupment; урожайність; productivity; пряма сівба; direct direct sowing